POLA ASUH IBU BEKERJA DALAM MEMBERIKAN MOTIVASI BELAJAR KEPADA ANAK (STUDI DESKRIPTIF ANALISIS DI SMA NEGERI 3 CIMAHI) - Puspita, Ayudha (2015)
The family is a small community that is the first cell of a large society, people are not going to have an existence without the presence of family. The family is also as the first school for children, where the child's family absorbs the In this family environment established of a process of personal care that mature to be able to live in a life as expected. Parenting in an ideal family happened when there is done by both parents. Father and mother work together hand in hand to provide care, guidance, motivation and education to their children. Based on the above, the formulation of the research are as follows: 1) How to use parenting working mother to child at SMAN 3 Cimahi, 2) How the mother works in motivating children to learn in SMAN 3 Cimahi, 3) what factors influence the selection of a mother's parenting work to provide the motivation to learn to children in SMAN 3 Cimahi. This study used a qualitative approach with case study method. A qualitative approach is used to obtain in-depth data, the data implies. Data collection techniques in this study using observations, interviews, and documentation. The results showed that parenting used by working mothers to their children who attend school in SMAN 3 Cimahi are vary depending on social status, environmental conditions and practices applied in the family. In this study, the parenting very dominant in this case is a democratic parenting. While the mother works in a way to motivate learning to children, has its own way of providing learning motivation in accordance with applicable parenting in the family. And there are many factors that influence the selection of working mothers parenting in providing motivation to learn to their children, including environmental factors, cultural factors and socioeconomic status factor